Penentu Faktor Fundamental dan Belanja Modal Terhadap Harga Saham Perusahaan Fast Moving Consumer Goods yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Putra, Rizky Dwi (Politeknik Ganesha Medan, 2024)
Each company is competing to advance its business in order to maximize profit from the business activities it engages in and to confront yearly competition. This study aims to investigate fundamental factors such as earning per share, return on asset, return on equity, book value per share, and capital expenditure on the stock prices of fast-moving consumer goods companies listed on the Indonesian Stock Exchange from 2017 to 2021. 99 samples of corporations listed on the Indonesian Stock Exchange are involved in the fast-moving consumer goods industry. The method of data analysis utilized in this investigation is multiple regression analysis. The results of this study is arning per share, return on asset, return on equity, book value per share, and capital expenditure have a significant impact on the stock prices simultaneously. Partially Earning per share, return on asset, return on equity, book value per share has a significant and positive effect on stockprice while capital expenditure has an insignificant effect. Implication of this study is company must always maintain and improve its financial and operational performance to maintain positive investor sentiment and capital market signals. Future research can employ objects from company listed on the Indonesian stock exchange with positive capital expenditure performance